Peculiarities of the Perioperative Care of Elderly Patients Undergoing Endoscopic Transsphenoidal Removal of Tumors in the Chiasmatic-Sellar Area - Alexey B. Kurnosov; Andrey Yu. Lubnin; Pavel L. Kalinin (Общая реаниматология, 2017)
Nowadays, in the age of rapid introduction of digital and fiber-optic technologies in neurosurgery, a technique for removal of tumors in the chiasmatic-sellar area via an endoscopic transsphenoidal endonasal approach is actively developed; this technique is considered less invasive and is well tolerated by patients, thus permitting to operate patients with somatic complications, as well as the elderly. Taking into account these facts, as well as world statistic data indicating a continuous trend of population aging in developed countries, including Russia, optimization of the perioperative care of elderly patients with a tumor of the chiasmatic-sellar area becomes the problem of highest priority. In order to solve it, this review discusses the basic peculiarities of the perioperative management of elderly patients (characteristics of their somatic status and possible variants of the pre-operational state) with a pathology in the chiasmatic-sellar region; it also presents the modern and most acceptable alternative solutions of this difficult problem (introduction of modern methods of anesthesia, management of the postoperative cognitive dysfunction, postoperative pain syndrome, and postoperative nausea and vomiting).